Hubungan pelaksanaan senam hamil dengan lama persalinan kala II pada ibu primigravida di Wilayah Kerja Puskesmas Padangmatinggi Kota Padangsidimpuan Tahun 2018 - Batubara, Novita Sari; Dewi, Sri Sartika Sari (Universitas Aufa Royhan, 2018)
Pregnancy gymnastics is a motion exercise therapy given to pregnant women to prepare themselves, both physical and mental preparation to deal with and prepare for a fast, safe, and spontaneous labor. The purpose of this study was to determine the relationship of pregnancy exercise implementation with the second stage of labor in the mother of primigravida in Padangmatinggi health centers Padangsidimpuan 2018. The research design was analytic observational with the design of the porspective cohort study. The population of this study is all Primigravida pregnant women in Padangmatinggi health centers area in 2018 which amounted to 40 people. The sample in this study is primigravida pregnant women in Padangmatinggi health center area in 2018, which estimated that the Birth Date is estimated in June as many as 40 people. The research instrument used questionnaires and statistical test used was Spearman's rho at 95% significance level (α = 0.05) where the value of p <α, which means the alternative hypothesis is accepted. The results showed that most of the active respondent mother exercised as many as 32 respondents (80.0%) and inactive as many as 8 respondents (20.0%). Respondent with normal second stage childbirth that was 30 respondents (75.0%) and abnormal as many as 10 respondents (25.0%). Based on statistical test using Spearman's rho obtained p-value value 0,001 (<0,05) and correlation coefficient (τ) = 0,866. . So it can be concluded that there is a relationship of pregnancy exercise implementation with the second stage of labor in the mother of primigravida in Padangmatinggi health centers Padangsidimpuan 2018. It is expected for pregnant women to actively perform pregnancy exercises during pregnancy, so that in the process of labor can run smoothly. For health services, can be the basis and input in improving health services in pregnant women and maternity, especially in the implementation of pregnancy exercise.